Nasaid na yaman - Papag, Ron Magbuhos; Guzman, Ros-B. ([Manila] Ibon Foundation, 1998)
A documentary on the degradation of Philippine natural resources brought about by industrialization.
VHS.
Isang produksyon ng People's Education Resource Center (PERC), IBON Foundation, Inc. sa tulong ng Dan ChurchAid.
Keywords: Environmental science